Peptide-Based siRNA Nanocomplexes Targeting Hepatic Stellate Cells - Chien-Yu Lin; Umar-Farouk Mamani; Yuhan Guo; Yanli Liu; Kun Cheng (Biomolecules, 2023)
Liver fibrosis is the excessive accumulation of extracellular matrix (ECM) in the liver due to chronic injuries and inflammation. These injuries activate and transform quiescent hepatic stellate cells (HSCs) into proliferative myofibroblast-like cells, which are the key contributors to the secretin of ECM in the fibrotic liver. The insulin-like growth factor 2 receptor (IGF2R) is a multifunctional receptor that is overexpressed on activated HSCs and is a specific molecular marker of activated HSCs in the fibrotic liver. We recently discovered an IGF2R-specific peptide that significantly increases the binding affinity and uptake of a protein-based siRNA nanocomplex to activated HSCs. However, there is a potential concern about the immunogenicity of protein-based siRNA delivery systems. In this study, we used the IGF2R-specific peptide to modify a small peptide-based siRNA nanocomplex for HSC-specific drug delivery. We incorporated a short spacer and glutamate residues into the IGF2R peptides. The siRNA nanocomplex modified with the IGF2R-3GK6E peptide demonstrated higher HSC specificity compared to an unmodified nanocomplex. This peptide-based nanocomplex provides a promising platform to effectively deliver Pcbp2 siRNA to activated HSCs for the treatment of liver fibrosis.